The life cycle of phagosomes: formation, maturation, and resolution. Issue 1 (September 2016) - Levin, Roni; Grinstein, Sergio; Canton, Johnathan
Summary: Phagocytosis, the regulated uptake of large particles (>0.5 μm in diameter), is essential for tissue homeostasis and is also an early, critical component of the innate immune response. Phagocytosis can be conceptually divided into three stages: phagosome, formation, maturation, and resolution. Each of these involves multiple reactions that require exquisite spatial and temporal orchestration. The molecular events underlying these stages are being unraveled and the current state of knowledge is briefly summarized in this article.